Pengaruh Sales Promotion dan Live Streaming terhadap Impulse Buying: Studi Kasus Produk Febtatto di Shopee - Agustin Azzahra, Mega; Fathy Shiroth, Salman; Wibowo, Edi (Jurnal Informatika Terpadu, 2025)
The development of technology has made online shopping increasingly popular in Indonesia. Shopee, as one of the largest online shopping platforms, continues to seek ways to attract buyers using sales promotion and live streaming. This study analyzes the effectiveness of these strategies through a case study of the Febtatto brand, using the Stimulus-Organism-Response (SOR) model to understand the psychological mechanisms behind impulse buying behavior. Using a quantitative approach, data was collected from 100 Febtatto customers on Shopee through an online survey and analyzed using PLS-SEM technique. Results show that sales promotion (β = 0.39) and live streaming (β = 0.312) significantly influence impulse buying (p < 0.05). Live streaming proves to be a stronger stimulus in driving impulse buying responses compared to sales promotion. These findings provide valuable insights for businesses in optimizing digital marketing strategies, particularly in integrating interactive elements such as live streaming with sales promotion to increase sales effectiveness.